Analysis of volatile organic compounds in crumb and crust of different baked and toasted gluten‐free breads by direct PTR‐ToF‐MS and fast‐GC‐PTR‐ToF‐MS. (17th August 2018) - Pico, Joana; Khomenko, Iuliia; Capozzi, Vittorio; Navarini, Luciano; Bernal, José; Gómez, Manuel; Biasioli, Franco
Abstract: Proton transfer reaction (PTR)‐time of fight (ToF)‐mass spectrometry (MS) has been recently employed as a quick, easy, and sensitive alternative to gas chromatography MS for the analysis of volatile compounds in food. In the present work, PTR‐ToF‐MS was applied to the characterization of the volatile profiles of the baked and toasted crumbs and crusts of 5 gluten‐free breads elaborated with quinoa, teff, and rice flours as well as corn and wheat starches and wheat bread as a control samples. Two hundred fifty‐nine peaks ( m / z ) were detected, 86 peaks were tentatively identified, and 56 volatile compounds were selected as important contributors to bread aroma. Fast gas chromatography PTR‐ToF‐MS analyses were performed with 42 standards to identify them in the baked crumbs and crusts, 18 of them being present in all the samples. From the baked samples, it was concluded that quinoa crust was the 1 with higher volatile compound in high abundance, characterized by volatile compounds from fermentation, lipid oxidation, 2‐acetyl‐1‐pyrroline, and diethyl‐pyrazines, while wheat crust was characterized by the highest content in furan derivatives. The toasting time led to crust samples with an increased content in all the volatile compounds: Quinoa crust was now characterized by the highest content in all the pyrazines and furan derivatives, while starches were distinguished by the highest abundance in 2‐acetyl‐1‐pyrroline and diethyl‐pyrazines. Neither the baked crumbs nor the toasted crumbs presented the highest content in none of the volatile compounds. Therefore, it was concluded that quinoa flour can be a suitable alternative for the elaboration of baked and toasted breads due to the high content of pleasant volatile compounds from fermentation, the key volatile in crust 2‐acetyl‐1‐pyrroline (baked sample), as well as pleasant pyrazines and toasted‐like furan derivatives (baked and toasted samples); however, the off‐flavor volatile compounds from lipid oxidation as well as the bitter saponins present in quinoa bread should be taken into account.